Annotated catalogue of the click-beetle genera Hapatesus Candѐze, 1863 and Toorongus Neboiss, 1957 (Coleoptera: Elateridae) from the Australasian realm - Hoffmannova, Johana; Kundrata, Robin (Zootaxa, 2020)
An annotated catalogue of the genera Hapatesus Candѐze, 1863 and Toorongus Neboiss, 1957 (Coleoptera: Elateridae) is presented. Altogether, 21 species are classified in Hapatesus (of which five in the subgenus Minutesus Neboiss, 1957), and four in Toorongus. The species of Hapatesus are distributed in Australia, New Guinea, the Bismarck Archipelago and New Zealand, and there are also dubious reports from Taiwan, India and Uganda. Toorongus, on the other hand, is an endemic of Australia. For each taxon we provide synonyms, information on types, type localities, distribution, and bibliography. The systematic placement and distribution of the above-mentioned genera are briefly discussed.